Inclusive Development through Municipal Governance: Issues and Prospects - Sodhi, Inderjeet Singh; Jha, Ashish (Advances in Social Sciences Research Journal, 2021)
Since decades the debate is going on about development where social, economic, cultural political etc. In recent years, there has been a growing call for “inclusive development” to meet contemporary development needs and challenges. It is argued that although economic growth is necessary, but it is not sufficient on its own in improving the welfare of a population. The time demands for such a development approach which can ensure that benefits of growth are shared equitably across all parts of society, particularly large groups of vulnerable poor populations. In Indian context inclusion and exclusion have multiple dimensions as the country has lot of heterogeneity and diversity in terms of many things it may culture, language, beliefs, geographical location, educational status, caste, religion, creed, races etc. So, it is very common that the level or depth of inclusion and exclusion also differs in larger sense for example a large portion of Indian population living in rural areas and rest living in urban areas and apart from that there are some areas comes under union territories, autonomous council, tribal areas etc. Keeping in view, of this dynamics, each area people has different needs and concerns and their visualization and expectation of inclusion and exclusion also differs. Therefore, each area has different system of governance structure at local level as it has very important role to cater the needs and concerns of people. In this context, the research study explores the role and efficacy of municipal governments in ensuring inclusive development. The paper also highlights the major issues in the process and put forward suggestions.